2013
DOI: 10.1016/j.febslet.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Redox modification of proteins as essential mediators of CNS autophagy and mitophagy

Abstract: Production of cellular reactive oxygen species (ROS) is typically associated with protein and DNA damage, toxicity, and death. However, ROS are also essential regulators of signaling and work in concert with redox-sensitive proteins to regulate cell homeostasis during stress. In this review, we focus on the redox regulation of mitophagy, a process that contributes to energetic tone as well as mitochondrial form and function. Mitophagy has been increasingly implicated in diseases including Parkinson’s, Amyotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 99 publications
1
23
0
Order By: Relevance
“…ROS generated from mitochondria and NADPH oxidases have been demonstrated to be essential to autophagy activation (2, 29, 30). Increased ROS induce autophagy activation via oxidative modification of proteins that is involved in either the autophagy machinery or autophagic cell signaling (20). Hydrogen peroxide has been shown to oxidize and subsequently inactivate Atg4 during starvation.…”
Section: Discussionmentioning
confidence: 99%
“…ROS generated from mitochondria and NADPH oxidases have been demonstrated to be essential to autophagy activation (2, 29, 30). Increased ROS induce autophagy activation via oxidative modification of proteins that is involved in either the autophagy machinery or autophagic cell signaling (20). Hydrogen peroxide has been shown to oxidize and subsequently inactivate Atg4 during starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though posttranslational protein modifications represent a molecular hallmark of pathologies associated with redox dysregulation such as neurodegeneration, atherosclerosis, and diabetes, only limited research has examined the occurrence of protein epitopes derived from chemical adduction by RCS in human skin in response to solar UVR [29, 44, 45]. Remarkably, formation of MDA-derived protein adducts in skin exposed to solar UVR has not been investigated before, even though these epitopes are known to accumulate in tissue under conditions of pathologic oxidative stress [4648].…”
Section: Discussionmentioning
confidence: 99%
“…154 ROS and/or redox imbalance-sensitive PTMs of metabolic enzymes, oncogenes, tumor-suppressor transcription factors and signaling molecules may play considerable roles in metabolic reprogramming. The PTMs on these proteins identified to be modulated by redox changes in cancer cells are phosphorylation, nitration, cysteine oxidation, glutathionylation, acetylation, methylation and SUMOylation (Figure 3), 19, 155, 156, 157, 158, 159 and studies showed acetylation of most enzymes functioning in glycolysis and the Krebs cycle. 160, 161 Oxidative stress induced with menadione affects the activities of core metabolic enzymes, such as PDH, IDH, fumarase, GAPDH, malic enzyme and citrate synthase, as well as levels of various metabolites from glycolysis and the Krebs cycle.…”
Section: Influence Of Oxidative Stress On Metabolic Enzymesmentioning
confidence: 99%